Facile, sensitive and reagent-saving smartphone-based digital image colorimetric assay of captopril tablets enabled by long-pathlength RGB acquisition - Thana Thanayutsiri; Thapakorn Charoenying; Prasopchai Patrojanasophon; Boonnada Pamornpathomkul; Praneet Opanasopit; Tanasait Ngawhirunpat; Theerasak Rojanarata (Pharmacia, 2023)
A new assay of captopril (CTP) tablets was developed based on digital image colorimetry using Ellman’s reagent. For the first time, a facile technique of increasing the analytical path was applied in this work to enhance the sensitivity. For this purpose, the reaction solutions were photographed using a smartphone while they were contained in two 1-cm pathlength cuvettes which were placed side by side. The Red-Green-Blue (RGB) in term of [B/(R+G+B)] was used to plot a standard curve. Compared to using a single cuvette, double cuvettes resulted in more precise analytical signals and better linearity (r2 of 0.9992). Additionally, CTP could be analyzed at low concentrations (2.5–25 µM) with LOD of 0.70 µM and LOQ of 2.13 µM, thus lowering the reagent consumption. The assay was proven to be valid, and it was greener, faster, and more affordable than the pharmacopeial chromatographic method, thereby suitable for pharmaceutical quality control.